Towards the establishment of a WACE examination in Japanese as a heritage language: Critical perspectives - Hasegawa, Hiroshi (Springer, 2014)
Learning languages Other Than English (LOTE) has been recognised as a vital element of Australia’s current school educational program. The Western Australian Certificate of Education (WACE), the highest secondary school award in Western Australia, enables students to take either English or another LOTE as a second language. For examples, students who are native speakers of English can take a WACE subject, say in Japanese, while students with Japanese as their first language can take English as their second language. However, while this would seem to cater for the needs of both students, it causes a dilemma for others. Those whose parent(s) speak Japanese as native speakers, but who were born or grew up in Australia are eligible to take WACE in either English as a second language or Japanese as a LOTE but may end up taking neither if they are considered to be native speakers of both languages. The School Curriculum and Standards Authority in WA has been handling such issues on a case-by-case basis, and it is not unusual to find students who feel forced to abandon their language learning completely for heritage language education, which can no longer be regarded as isolated or rare. This chapter discusses the challenges and implications of the establishment of a WACE in Japanese as a heritage language.